Analisis Perilaku Konsumen pada Mini Market 212 Martujung Harapan Bekasi - Elva Muntazia; Diana Prihandini (JAMBIS : Jurnal Administrasi Bisnis, 2021)
The awakening spirit of the people during 212 rally had formeda  forum to advance the economy of Muslim people :212 Sharia Cooperative,and had initiated the birth  of 212 Mart,  an Islamic mini market with the concept of sharing economy. The concept was different from the concept the   previously  existing  mini markets.  The implementation  of sharing economy concept was highly appropriate and suitable with the basic principle soft rade according to Islam. Based on the result of the study analyzed,the customers especially Muslims responded and welcomed the presence of 212 Mart well. The factors that affected the customers indeciding to buy at 212 Mart were cultural, social, production/personal,  and factor psychological  factors.However, the factors that  kept the customers from buying at  212 Mart included the ongoing Covid-19 pandemic,incomplete products, higher price forsome products, andnot quiterecognized bythesociety. Theresearch methodused was descriptive qualitative. The data collection  techniques used were observation,interview,and documentation.